Sludge ash for concrete as well as preparation method and application of sludge ash
Sewage sludge ash with tailored composition and processing is used to replace fly ash in concrete, enhancing strength and durability, and facilitating resource recycling.
Patent Information
- Application Number
- CN202411409461.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-10
- Publication Date
- 2025-01-03
AI Technical Summary
Sewage sludge ash directly used in concrete preparation has an unreasonable phase composition and poor hydration reaction effect, leading to a loose structure, poor strength, and low durability, with limited replacement capacity for fly ash and potential for concrete cracking and setting issues due to high alkali metal oxides and sulfates.
Sewage sludge ash with specific composition (10-15% Al2O3, 15-25% Fe2O3, 30-40% SiO2, 15-20% CaO, controlled SO3, MgO, K2O, TiO2, ZnO, Na2O, P2O5, CuO content, and particle size <75 μm) is used to replace 100% fly ash, processed through calcining, grinding, and screening, and mixed with silicate cement and standard sand to form cement-based concrete.
The solution achieves high compressive and flexural strength, resource recycling of sewage sludge waste, and reduces concrete production costs while ensuring a dense structure and improved durability.
Smart Images

Figure CN119241108A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of building materials, and in particular to sewage sludge ash for concrete and a preparation method and application thereof. Background Art
[0002] Fly ash is widely used in the field of building materials because it can improve the workability of fresh concrete, reduce the water consumption of concrete, and inhibit alkali-aggregate reaction. However, fly ash resources are currently in short supply. Therefore, finding a suitable fly ash substitute is one of the important research directions for the future of concrete and the entire construction industry.
[0003] Sludge treatment is a key direction in my country's waste treatment field. Urban sewage and factory wastewater contain a large amount of wet sludge rich in bacteria, microorganisms, heavy metal pollutants and other complex components. At present, sludge incineration technology is one of the mainstream technologies for sludge treatment in China. This method can not only achieve the maximum reduction and stabilization of sludge, but also prevent the secondary pollution caused by direct landfill of sludge. If the incinerated sludge ash is used to replace fly ash in the production of concrete, this application can not only fill the demand for fly ash in the construction field, but also realize the resource utilization of sludge cooked ash, so it is of great significance.
[0004] However, using sludge ash directly as a cement admixture to prepare concrete has a poor effect. This is because the unmodified sludge ash lacks activity and is not easy to form a dense structure with other components during the hydration reaction, resulting in a loose structure of the prepared concrete, poor strength, and low durability. In addition, some sludge ash contains relatively high alkali metal oxides or sulfates. During the hydration reaction, the alkaline oxides react chemically with the silica contained in the aggregate, causing the concrete to easily expand and crack; in addition, excessive sulfate content will also cause the concrete to slow set.
[0005] In the prior art, a Chinese patent with publication number CN106747086B discloses an ecological permeable concrete based on sludge incineration ash and a preparation method. The technical solution is composed of a certain proportion of sludge incineration ash, cement, water reducer, crushed stone, etc. The technical solution can prepare concrete with both high compressive strength and excellent permeability, and the compressive strength after 28 days can reach up to 32.0MPa. However, sludge ash can only replace 15wt% of the cement mass in concrete at most; in addition, the particle size of the sludge incineration ash in the technical solution is 18-20μm, and too small a particle size will increase water consumption, thereby affecting the effect of the hydration reaction.
[0006] The Chinese patent with publication number CN112624646A discloses a concrete admixture, wherein the components of the sludge ash X-ray fluorescence spectrum detection are: by weight, SO3 content is 20-40 parts, CaO content is 30-60 parts, SiO2+Al2O3 content is 5-40 parts, Cl content is <0.1 parts, K2O+Na2O content is <1 parts, MgO is <10 parts, and other components including Fe2O3+P2O5 are <10 parts. The sludge ash of this technical solution can replace 20-50wt% of the cement mass, but the maximum compressive strength under different replacement ratios is only 20.7MPa. Summary of the invention
[0007] The present invention aims at the problem that the phase composition of sewage sludge ash is unreasonable and the hydration reaction effect is poor when sewage sludge ash is directly used in concrete preparation, and provides sewage sludge ash for concrete and its preparation method and application. The sewage sludge ash for concrete provided by the present invention is used to replace 100% of fly ash, and the mixing amount in cement-based concrete is as high as 60%, which can achieve the technical effect of high compressive strength and high flexural strength of concrete, and realizes the resource recycling of sewage sludge waste pollutants while reducing the cost of concrete use.
[0008] To achieve the above purpose, the technical solution adopted by the present invention is as follows:
[0009] The first aspect of the present invention provides sewage sludge ash for concrete, wherein the sewage sludge ash for concrete contains 10-15% by mass of Al2O3, 15-25% by mass of Fe2O3, 30-40% by mass of SiO2, and 15-20% by mass of CaO.
[0010] Preferably, the sewage sludge ash for concrete contains Al2O3 of 12% by mass, Fe2O3 of 20.6% by mass, SiO2 of 34.5% by mass, and CaO of 17.2% by mass.
[0011] Preferably, the sewage sludge ash for concrete also contains trace components such as MgO, SO3, K2O, TiO2, ZnO, Na2O, MnO, P2O5 and CuO.
[0012] Preferably, the mass fraction of SO3 contained in the sewage sludge ash for concrete is less than 9%.
[0013] Preferably, the mass fraction of P2O5 contained in the sewage sludge ash for concrete is less than 2.5%.
[0014] Preferably, the mass fraction of MgO contained in the sewage sludge ash for concrete is less than 1.2%.
[0015] Preferably, the mass fraction of K2O contained in the sewage sludge ash for concrete is less than 1.8%.
[0016] Preferably, the mass fraction of TiO2 contained in the sewage sludge ash for concrete is less than 0.8%.
[0017] Preferably, the mass fraction of ZnO contained in the sewage sludge ash for concrete is less than 0.5%.
[0018] Preferably, the mass fraction of other trace components contained in the sewage sludge ash for concrete is less than 1%.
[0019] Preferably, the particle size of the sewage sludge ash for concrete is less than 75 μm.
[0020] The second aspect of the present invention provides a method for preparing the above-mentioned sewage sludge ash for concrete, comprising the following steps: calcining, grinding and screening the sewage sludge to obtain the sewage sludge ash for concrete.
[0021] Preferably, the calcination temperature is 700-900° C., and the calcination time is 1.5-3 h.
[0022] Preferably, the calcination temperature is 800° C. and the calcination time is 2 h.
[0023] Preferably, the grinding method is powder grinding, and the grinding time is 30-60s.
[0024] Preferably, the sieve is 200 mesh.
[0025] The third aspect of the present invention provides the use of the above-mentioned sewage sludge ash for concrete in the preparation of cement-based concrete.
[0026] A fourth aspect of the present invention provides a cement-based concrete, which comprises the above-mentioned sewage sludge ash for concrete, silicate cement, standard sand and water.
[0027] Preferably, the mass ratio of the sludge ash, silicate cement, standard sand and water for concrete is (0.4-1.2):
[0028] (0.8-1.6):6:1.
[0029] Preferably, the mass ratio of the sludge ash, silicate cement, standard sand and water for concrete is (0.4-0.8):
[0030] (1.2-1.6):6:1.
[0031] Preferably, the mass ratio of sewage sludge ash, silicate cement, standard sand and water for concrete is 0.4:1.6:6:1.
[0032] The fifth aspect of the present invention provides a method for preparing the above-mentioned cement-based concrete, comprising the following steps: mixing concrete with sludge ash, silicate cement, standard sand and water to obtain a slurry; and the slurry is successively subjected to molding, demolding and curing to obtain the cement-based concrete.
[0033] Preferably, the method for preparing the cement-based concrete comprises the following steps:
[0034] S1. Mixing: Pour Portland cement and sludge ash for concrete into the Hobart mixing pot, place the mixing pot on the fixed frame of the mixer, and raise it to a fixed position; start the mixer, stir at a low speed for 240s±3s, then pour water in and mix evenly for 90s±3s; after the mixing is completed, add standard sand into the mixing pot, and after adding the standard sand, turn the machine to high-speed mixing for 90s±3s to obtain slurry;
[0035] S2. Molding: Pour the slurry in the stirring pot into a 40mm×40mm×160mm prism mold, place the mold on a vibration table, and start the vibration table; after the vibration is completed, remove the prism mold, use a leveling ruler to scrape off the slurry that is higher than the test mold and smooth it; after the slurry is initially solidified, cover it with a plastic film and let it stand;
[0036] S3, demoulding: demoulding after standing for 24 hours;
[0037] S4, curing: after demoulding, the concrete is placed in a curing box and cured at 22° C. and 95% humidity to obtain the cement-based concrete.
[0038] Compared with the prior art, the present invention has the following beneficial effects:
[0039] (1) The sewage sludge ash for concrete with a specific composition according to the present invention can be used as a substitute for fly ash and can be used to replace 100% of fly ash.
[0040] (2) The mixing amount of the sewage sludge ash for concrete of the present invention in cement-based concrete can be as high as 60%.
[0041] (3) The cement-based concrete prepared by using the sewage sludge ash for concrete of the present invention when added in an amount of 20-60% by weight has higher compressive strength, flexural strength and activation index than that of fly ash.
[0042] (4) The sewage sludge ash for concrete provided by the present invention helps to reduce the production cost of concrete and realize the resource recycling of waste sewage sludge. BRIEF DESCRIPTION OF THE DRAWINGS
[0043] Figure 1 This is an electron microscope photograph of the microstructure of the hydration product of the cement in Application Example 1 after curing for 28 days;
[0044] Figure 2 This is an electron microscope photograph of the microstructure of the hydration product of the cement in Application Example 2 after curing for 28 days;
[0045] Figure 3 This is an electron microscope photograph of the microstructure of the hydration product of the cement in Application Example 3 after curing for 28 days;
[0046] Figure 4 The electron microscope photo of the microstructure of the hydration product of the cement of comparative application example 7 after curing for 28 days;
[0047] Figure 5 The electron microscope photo of the microstructure of the hydration product of the cement in comparative application example 8 after curing for 28 days;
[0048] Figure 6 The electron microscope photo of the microstructure of the hydration product of the cement of comparative application example 9 after curing for 28 days;
[0049] Figure 7 This is an electron microscope photo of the microstructure of the hydration product of the cement of comparative application example 10 after curing for 28 days;
[0050] Figure 8 This is the particle size distribution diagram of sewage sludge ash, Conch PII 52.5 ordinary Portland cement, and Class I fly ash for concrete in Example 1. DETAILED DESCRIPTION
[0051] The following non-limiting examples can enable those skilled in the art to more fully understand the present invention, but do not limit the present invention in any way. The following content is merely an exemplary description of the scope of the present invention, and those skilled in the art can make various changes and modifications to the present invention based on the disclosed content, which should also fall within the scope of the present invention.
[0052] The cement used in the following application examples and comparative application examples is Conch PII 52.5 ordinary Portland cement, and the fly ash is Class I fly ash; the standard sand comes from Xiamen Aiso Standard Sand Co., Ltd., and the sludge comes from Zhejiang Zhengjie Environmental Resources Co., Ltd.
[0053] Example 1 and Comparative Example 1-2 provide a kind of sewage sludge ash for concrete:
[0054] The mineral components in the sludge ash for concrete of Example 1 and Comparative Examples 1-2 and the mineral components in Class I fly ash and Conch PII 52.5 ordinary Portland cement were analyzed by X-ray diffraction (XRD) analysis and X-ray fluorescence (XRF) spectroscopy. The results are shown in Table 1.
[0055] Table 1
[0056]
[0057]
[0058] The method for preparing sewage sludge ash for concrete described in Example 1 comprises the following steps: calcining the original sewage sludge at 800°C for 2 hours, and finally grinding the sludge ash for concrete for 50 seconds using a QE series high-speed ore crusher, and passing the ground sewage sludge ash for concrete through a 200-mesh standard sieve, and vibrating the sludge ash for concrete in a vibrating sieve for 5 minutes, wherein the particle size of the sewage sludge ash for concrete is less than 75 μm.
[0059] The preparation method of the sewage sludge ash for concrete described in Comparative Example 1 comprises the following steps: calcining the original sewage sludge at 800°C for 2 hours, and finally grinding the sewage sludge ash for concrete for 50 seconds using a QE series high-speed ore crusher, and passing the ground sewage sludge ash through a 200-mesh standard sieve, and vibrating the sludge ash in a vibrating screen for 5 minutes to prepare the sewage sludge ash for concrete, wherein the particle size of the sewage sludge ash for concrete is less than 75 μm.
[0060] The preparation method of sludge ash for concrete described in Comparative Example 2 comprises the following steps: calcining the original sludge at 800°C for 2h, washing with water, and then drying it in an oven at 60°C for 24h, and finally grinding it for 50 seconds using a QE series ore high-speed crusher, and passing the ground sludge ash for concrete through a 200-mesh standard sieve, and vibrating it in a vibrating screen for 5min to prepare sludge ash for concrete, wherein the particle size of the sludge ash for concrete is less than 75μm.
[0061] Application Examples 1-3 and Comparative Application Examples 1-10 provide a cement-based concrete, the formula of which is shown in Table 2.
[0062] Table 2 Formulation (kg / m 3 )
[0063]
[0064]
[0065] The method for preparing the cement-based concrete described in Application Examples 1-3 and Comparative Application Examples 1-10 comprises the following steps:
[0066] S1. Mixing: Pour silicate cement, sludge ash or fly ash for concrete into the Hobart mixing pot, place the mixing pot on the fixed frame of the mixer, and raise it to a fixed position; start the mixer, stir at a low speed for 240s±3s, then pour water in and mix evenly for 90s±3s; after the mixing is completed, add standard sand into the mixing pot, and after adding the standard sand, turn the machine to high-speed mixing for 90s±3s to obtain slurry;
[0067] S2. Molding: Pour the slurry in the stirring pot into a 40mm×40mm×160mm prism mold, place the mold on a vibration table, and start the vibration table; after the vibration is completed, remove the prism mold, use a leveling ruler to scrape off the slurry that is higher than the test mold and smooth it; after the slurry is initially solidified, cover it with a plastic film and let it stand;
[0068] S3, demoulding: demoulding after standing for 24 hours;
[0069] S4, curing: after demoulding, the concrete is placed in a curing box and cured for 56 days at 22° C. and 95% humidity to obtain the cement-based concrete.
[0070] Test example:
[0071] 1. Test of compressive strength, flexural strength and activity index of cement-based concrete:
[0072] The compressive strength and flexural strength of the cement-based concrete (cured for 28 days) prepared by corresponding Example 1-3 and Comparative Application Example 1-10 were determined according to the requirements of standard GB / T17671-2021 "Test method for strength of cement mortar (ISO method)", and the activity index of the cement-based concrete was determined according to GB / T 51003-2014 "Technical Specification for Application of Mineral Admixtures". The results are shown in Table 3.
[0073] Table 3
[0074] Compressive strength(MPa) Flexural strength(MPa) Activity index (%) Application Example 1 54.9 8.3 102 Application Example 2 45.6 7.9 85 Application Example 3 22.6 4.4 42 Comparative application example 1 28.8 4.3 54 Comparative Application Example 2 18.1 4.1 34 Comparative Application Example 3 13.2 4.0 25 Comparative Application Example 4 35.1 6.6 65 Comparative Application Example 5 24.3 4.1 45 Comparative Application Example 6 20.4 4.7 38 Comparative Application Example 7 52.3 8.7 97 Comparative Application Example 8 38.3 7.0 71 Comparative Application Example 9 19.6 4.8 36 Comparative Application Example 10 53.8 8.9 100
[0075] It can be seen from Table 3 that when the sewage sludge ash for concrete is mixed with silicate cement, the cement-based concrete of Application Examples 1-3 has better compressive strength, flexural strength and activity index than the cement-based concrete of Comparative Application Examples 1-6, and the cement-based concrete with a 20% mixing amount (Application Example 1) has comparable compressive strength, flexural strength and activity index to the unmixed sewage sludge ash for concrete (Comparative Application Example 10);
[0076] When fly ash is used to mix silicate cement, at the same mixing amount as sludge ash for concrete, especially at 40% (Comparative Application Example 8) and 60% (Comparative Application Example 9) mixing amounts, the compressive strength, flexural strength and activation index of cement-based concrete decrease.
[0077] 2. Cement-based concrete morphology test:
[0078] The cement of application examples 1-3 and comparative application examples 7-10 was subjected to hydration experiment with a water-cement ratio of 0.5, and cured for 28 days at 20±1°C and humidity>95% to obtain hydration products. The morphology of the hydration products was detected by SEM. The results are as follows: Figure 1-7The particle size distribution of the sludge ash, fly ash and silicate cement used in the concrete in the application example is shown in Figure 8 shown.
[0079] Depend on Figure 4-7 It can be seen that: Comparative Application Example 10 has a compact and dense structure due to sufficient hydration, while in Comparative Application Examples 7-9, as the fly ash content increases, it can be observed that the matrix structure gradually becomes loose, the interface uniformity of the concrete decreases, and some fly ash particles on the surface of the specimens that are wrapped by the gel are scattered after the specimens are broken. The generated CSH (Ca-Si-H2O) gel is not uniform and continuous, and the amount of AFt (calcium aluminate) is significantly reduced.
[0080] Depend on Figure 1-3 It can be seen that: as the amount of sewage sludge ash added to concrete increases in Application Examples 1-3, the matrix structure gradually becomes loose, the continuity of the generated CSH gel becomes worse, and the amount of AFt decreases significantly; but compared with Application Examples 7-9 with the same dosage, Application Examples 1-3 have significantly more hydration products and a tighter matrix structure. Figure 8 It can be seen that the particle size of sewage sludge ash for concrete is finer than that of fly ash, which means that sewage sludge ash for concrete can better fill the pores produced by the hydration reaction of concrete, which is also beneficial to the formation of a tight matrix structure and the realization of ultimate strength performance.
[0081] Emphasis: From Figure 3 6 and 7 can intuitively show the difference in the microstructure of concrete. Under 60wt% high-quality doping, the sludge ash concrete in Application Example 3 forms more three-dimensional cross-linked network CSH gel structure and AFt needle-shaped crystal structure than the fly ash concrete in Comparative Application Example 9. At the same time, it can be seen that part of the AFt in Application Example 3 is further converted into AFm (monosulfur calcium sulfoaluminate hydrate), and the microstructure is also more compact, indicating that the hydration of Application Example 3 is more complete and the activity of sludge ash is well released. At the same time, there is no obvious structural difference in the microstructure formed by pure silicate cement in Application Example 3 compared with Comparative Application Example 10. The comparison of microstructure photos shows that the hydration reaction effect of concrete with sludge ash is better.
[0082] Finally, it should be noted that the above content is only used to illustrate the technical solution of the present invention, rather than to limit the scope of protection of the present invention. Simple modifications or equivalent substitutions of the technical solution of the present invention by ordinary technicians in this field do not deviate from the essence and scope of the technical solution of the present invention.
Claims
1. A sludge ash for concrete, characterized in that: The sewage sludge ash for concrete contains Al2O3 of 10-15% by mass, Fe2O3 of 15-25% by mass, SiO2 of 30-40% by mass, and CaO of 15-20% by mass.
2. The sludge ash for concrete according to claim 1, characterized in that: The sewage sludge ash for concrete contains Al2O3 in a mass fraction of 12%, Fe2O3 in a mass fraction of 20.6%, SiO2 in a mass fraction of 34.5%, and CaO in a mass fraction of 17.2%.
3. The sludge ash for concrete according to claim 1, characterized in that: The particle size of the sewage sludge ash for concrete is less than 75 μm.
4. A method for preparing the sewage sludge ash for concrete according to any one of claims 1 to 3, comprising the following steps: The sludge ash for concrete is obtained after calcining, grinding and screening.
5. The preparation method according to claim 4, characterized in that: The calcination temperature is 700-900° C., and the calcination time is 1.5-3 hours.
6. The preparation method according to claim 5, characterized in that: The calcination temperature is 800° C. and the calcination time is 2 h.
7. Use of the sewage sludge ash for concrete according to any one of claims 1 to 3 in preparing cement-based concrete.
8. A cement-based concrete, characterized in that: The cement-based concrete comprises the sludge ash for concrete according to any one of claims 1 to 3, Portland cement, standard sand and water.
9. The cement-based concrete according to claim 8, characterized in that: The mass ratio of sewage sludge ash, silicate cement, standard sand and water for the concrete is (0.4-1.2):(0.8-1.6):6:
1.
10. A method for preparing cement-based concrete according to claim 8 or 9, characterized in that: The following steps are involved: The concrete is mixed with sludge ash, silicate cement, standard sand and water to obtain slurry; the slurry is successively formed, demolded and cured to obtain the cement-based concrete.
